Illuminating the ‘Face’ of Justice: A Meta‐Analytic Examination of Leadership and Organizational Justice - Karam, Elizabeth P.; Hu, Jinyu; Davison, Robert B.; Juravich, Matthew; Nahrgang, Jennifer D.; Humphrey, Stephen E.; Scott DeRue, D. (Journal of Management Studies, 2019)
AbstractA significant body of research has described effective leader behaviours and has connected these behaviours to positive employee outcomes. However, this research has yet to be systematically integrated with organizational justice research to describe how leader behaviours inform justice perceptions. Therefore, we conduct a meta‐analysis (k = 166, N = 46,034) to investigate how three types of leader behaviours (task, relational, and change) inform four dimensions of organizational justice (procedural, distributive, interpersonal, and informational) referenced to the leader and to the organization. Further, we examine the joint impact of leader behaviours and justice perceptions on social exchange quality (i.e., leader–member exchange), task performance, and job satisfaction. Our results suggest that leader behaviours differentially inform leader‐ and organization‐focused justice perceptions, and the joint effect of leader behaviours and justice perceptions offer more nuanced explanations for outcomes.